Heme Competition Triggers an Increase in the Pathogenic Potential of Porphyromonas gingivalis in Porphyromonas gingivalis-Candida albicans Mixed Biofilm - Guo, Yanyang; Wang, Yu; Wang, Yijin; Jin, Yabing; Wang, Chen (Frontiers in Microbiology, 2020)
As one of the main pathogens of periodontitis, Porphyromonas gingivalis often forms mixed biofilms with other bacteria or fungus under gingiva, such as Candida albicans. As an important iron source for P. gingivalis and C. albicans, heme supports their growth in the host. From the perspective of heme competition, this study aims to clarify that the competition for heme enhances the pathogenic potential of P. gingivalis during the interaction between P. gingivalis and C. albicans. P. gingivalis single-species biofilm and P. gingivalis-C. albicans dual-species biofilm were established in a low and high heme environment. The results showed that the vitality of P. gingivalis was increased in the dual-species biofilm under the condition of low heme, and the same trend was observed under the laser confocal microscope. Further, the morphological changes of P. gingivalis were observed by electron microscope, and P. gingivalis in dual-species biofilm can better resist the killing effect of healthy human serum and antibiotics. The ability of P. gingivalis to agglutinate erythrocyte can also be enhanced in dual-species biofilm. These changes disappeared when heme was sufficient, which confirmed that heme competition was the cause of pathogenicity change of P. gingivalis. Gene level analysis showed that P. gingivalis was in a superior position in the competition relationship by improving the expression of heme utilization related genes such as HmuY, HmuR, HusA, Tlr. In addition, the expression of genes encoding gingipains (Kgp, RgpA/B) was also significantly increased. They not only participate in the process of utilizing heme, but also are important components of the virulence factors of P. gingivalis. In conclusion, our results indicated that the pathogenic potential of P. gingivalis was enhanced by C. albicans through heme competition, ultimately promoting the occurrence and development of periodontitis and, therefore, C. albicans subgingival colonization should be considered as a factor in assessing the risk of periodontitis.